2022
DOI: 10.1097/md.0000000000030273
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis from colorectal cancer: Treatment, survival, and prognosis

Abstract: To investigate the clinical characteristics, survival, prognostic factors, and treatment of brain metastasis (BM) from colorectal cancer (CRC). Twenty-one patients with BM from CRC were retrospectively reviewed. Predictive factors for BM and prognostic factors after the diagnosis of BM were examined by univariate and multivariate COX analysis. The time from the development of extracranial metastases, including lung, bone, and liver, to the occurrence of BM was recorded separately. The median overall survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Similarly, Nozawa et al and Thompson et al showed that lung and bone metastases were independent predictive factors for BM in CRC [2,14]. In addition, previous studies have reported that the median interval from lung metastasis to BM was 8-11 months, the median interval from liver metastasis to BM was 6.5 months, and the median interval from bone metastasis to BM was 3 months [22,23]. We found that the median time interval from liver metastasis to BMs was 8 months.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Nozawa et al and Thompson et al showed that lung and bone metastases were independent predictive factors for BM in CRC [2,14]. In addition, previous studies have reported that the median interval from lung metastasis to BM was 8-11 months, the median interval from liver metastasis to BM was 6.5 months, and the median interval from bone metastasis to BM was 3 months [22,23]. We found that the median time interval from liver metastasis to BMs was 8 months.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, with increased utilization of brain imaging, the incidence of brain metastases from CRC continues to increase. Hence, finding effective treatments for BM from CRC is of paramount importance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the utilization of systemic therapy in patients with BMs has been limited by the presence of the blood–brain barrier (BBB), which restricts the entry of hydrophilic and/or large drugs into the brain.) [ 5 , 12 , 19 , 20 ]. Another consideration that might explain the disappointing results of chemotherapy in BM is the fact that metastatic cells in the brain often develop late in the course of the disease; after several rounds of prior chemotherapy for the systemic disease, allowing for the development of resistance through the accumulation of various mutations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations